A Novel LTPS-TFT Pixel Circuit to Compensate the Electronic Degradation for Active-Matrix Organic Light-Emitting Diode Displays - Ching-Lin Fan; Fan-Ping Tseng; Hui-Lung Lai; Bo-Jhang Sun; Kuang-Chi Chao; Yi-Chiung Chen (International Journal of Photoenergy)
A novel pixel driving circuit for active-matrix organic light-emitting diode (AMOLED) displays with low-temperature polycrystalline-silicon thin-film transistors (LTPS-TFTs) is studied. The proposed compensation pixel circuit is driven by voltage programming scheme, which is composed of five TFTs and one capacitor, and has been certified to provide uniform output current by the Automatic Integrated Circuit Modeling Simulation Program with Integrated Circuit Emphasis (AIM-SPICE) simulator. The results of simulation show excellent performance, such as the low average error rate of OLED current variation (<0.5%) and the low average nonuniformity of OLED current variation (<0.8%) while the shift of threshold voltage of the driving poly-Si TFT and the OLED are both in the worst case ( V for TFT and  V for OLED). The proposed pixel circuit shows high immunity to the threshold voltage deviation of both the driving poly-Si TFT and the OLED.